Entrepreneurship and Brand Building in Niche Luxury Markets: Cross-Industry Insights From the UAE - El Obaid, Aseel Abdelrahman (Digital Repository of Theses, 2026)
This study explores how niche luxury entrepreneurs in the United Arab Emirates (UAE) construct, communicate, and sustain brand identity within a competitive, globalized, and culturally hybrid market. Positioned within a rapidly evolving creative economy that emphasizes innovation alongside heritage preservation, the UAE provides a distinctive context for examining how luxury value and legitimacy are created in the absence of long-established historical lineage. The research focuses on founders and senior managers operating across fashion, jewelery, fragrance, aviation, and lifestyle sectors, examining how luxury is redefined through entrepreneurial practice, cultural meaning, and strategic brand-building, including how entrepreneurs understand and respond to consumer expectations. A qualitative research design was adopted, drawing on twenty semi-structured interviews with niche luxury founders and senior managers based in the UAE. The data were analysed using a systematic thematic analysis approach, enabling the identification of recurring patterns, meanings, and strategic practices grounded in participants lived experiences. This approach facilitated an in-depth understanding of entrepreneurial sense-making processes, symbolic value creation, and culturally embedded branding practices that are often underrepresented in quantitative luxury research. The findings reveal that niche luxury entrepreneurs in the UAE construct brand identity and legitimacy through narrative-driven and culturally grounded strategies rather than inherited heritage. Six interconnected themes emerged: Cultural Identity and Storytelling; Exclusivity and Accessibility; Digital Storytelling and Communication; Trust, Craftsmanship, and Provenance; Entrepreneurial Challenges and Strategies; and Future Orientation and Sustainability. Entrepreneurs actively employ cultural storytelling, founder visibility, craftsmanship, transparency, and controlled exclusivity to establish authenticity and credibility. Digital platforms function as enablers of relational engagement and global reach, while ethical practices and sustainability increasingly shape entrepreneurs perceptions of consumer expectations and competitive positioning. The study contributes to contemporary understandings of luxury entrepreneurship by demonstrating that legitimacy in emerging luxury markets can be actively constructed through cultural alignment, symbolic meaning, and entrepreneurial agency. It challenges Western-centric luxury models by presenting a context in which luxury is defined less by historical lineage and more by authenticity, emotional connection, and cultural relevance. The findings offer valuable insights for entrepreneurs, brand managers, and policymakers seeking to support culturally grounded and globally competitive luxury ventures in emerging markets.